Dilema Etis dalam Periklanan dalam Upaya Mengatasi Kontroversi - Nur Hidayat Saputra; Abdul Muiz Aldzakir; Apriliono Teguh Aditya; Daniel Handoko (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The ethical dilemmas in advertising have long posed significant challenges for marketers and organizations. This paper aims to explore these dilemmas, highlighting the controversy often associated with advertising practices. Through a detailed examination of case studies and theoretical frameworks, we provide insights into the strategies employed by companies to navigate these ethical challenges. The study concludes with recommendations for more ethical advertising practices that align with both consumer expectations and regulatory standards.